Epidemiological profile of tobacco users attending a tobacco cessation centre at Puducherry, India - S Saravanan; Kuppusamy Rajagopal Lenin (Wolters Kluwer Medknow Publications, 2022)
Background: Tobacco is a major health burden and an effort has been made to help users to quit tobacco by establishing a tobacco cessation centre in our Institution. A knowledge on the extent of distribution of tobacco use across the various sub-groups of the users would provide clues to behavioural patterns. Objective: To describe the epidemiological profile of tobacco users and to provide a baseline data about the attendees of the cessation centre. Materials and Methods: The data for the present descriptive evaluation were collected by reviewing of case records of participants enrolled from April 2014 to March 2015. Data on demographic characteristics, tobacco use details, substance use details and geographic profile were evaluated. Descriptive statistics were used to present the data using number and percentage. Results: Of the 621 current tobacco users, 95.5% were of male gender. Most participants were married (79.4%), literates (84.9%) and were in the fourth decade of life. 78.1% were exclusive Smokers, 18.2% were exclusive Smokeless tobacco (SLT) users and 3.7% were dual form users. "Peer pressure" was the major reason for initiation of the habit. "Cigarette" was used by 65% of the Smokers and "Betel quid with tobacco" was used by 36.6% of the SLT users. 86.1 and 13.9% of the Puducherry residents were smokers and SLT users respectively. "Oral potentially malignant disorders" were noted in 8% of the users. Conclusion: The observations of the present evaluation provide a baseline data which may serve as a starting point for future epidemiological enquiry.